2007
DOI: 10.1007/s00497-007-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic evaluation of gymnosperm pollination drop proteins indicates highly conserved and complex biological functions

Abstract: The pollination droplet is a highly conservative pollination mechanism that is observed in all major gymnosperm taxa. Proteomics analysis of the pollination drops was carried out on four gymnosperm species: Juniperus communis (common juniper), Juniperus oxycedrus (prickly juniper), Chamaecyparis lawsoniana (Port Orford cedar), and Welwitschia mirabilis. Pollination drop proteins were purified by SDS-PAGE, and the most abundant proteins were analyzed by mass spectrometry and sequenced. Based on BLAST searching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 28 publications
(38 reference statements)
4
58
1
2
Order By: Relevance
“…Fern nectaries produce watery, nutritionally poor secretions, whereas carbohydrate and amino acid concentrations of pollen drops from the four major lineages of gymnosperms-conifers, Ginkgo L., cycads, and gnetaleans-showed significantly more elevated nutritional levels, particularly in the two latter insectpollinated clades (Labandeira et al, 2007a). Nutritional levels in pollination drops of the four gymnosperm clades are similar to those of nectar from basal angiosperm lineages (Labandeira et al, 2007a;Wagner et al, 2007;Nepi et al, 2009). Lipid levels were not measured.…”
Section: Plant Features Associated With Haustellate Insect Pollinatorsmentioning
confidence: 66%
“…Fern nectaries produce watery, nutritionally poor secretions, whereas carbohydrate and amino acid concentrations of pollen drops from the four major lineages of gymnosperms-conifers, Ginkgo L., cycads, and gnetaleans-showed significantly more elevated nutritional levels, particularly in the two latter insectpollinated clades (Labandeira et al, 2007a). Nutritional levels in pollination drops of the four gymnosperm clades are similar to those of nectar from basal angiosperm lineages (Labandeira et al, 2007a;Wagner et al, 2007;Nepi et al, 2009). Lipid levels were not measured.…”
Section: Plant Features Associated With Haustellate Insect Pollinatorsmentioning
confidence: 66%
“…Extrafloral nectar also has its own enzymatic defense against invasion by micro-organisms, the predominant enzymes being chitinase, ␤-1,3-glucanase and thaumatine-like proteins . Defense proteins such as glucosidases, chitinases, hydrolases, and thaumatine-like proteins have also been detected in pollination drops (Wagner et al, 2007), secretions produced by the ovules of gymnosperms and that possess a chemical composition similar to that of angiosperm nectar (Nepi et al, 2009).…”
Section: Proteins For Nectar Defence and ˇ-Xylosidases In C Pepo Nectarmentioning
confidence: 98%
“…Experimental evidence for chitinases acting as defense proteins has been obtained using transgenic plants that overexpressed chitinases and exhibited higher resistance to pathogens (Schlumbaum et al 1986;Broglie et al 1991;Minic 2008). Wagner et al (2007) firstly detected chitinase (class IV, GH19 family) in pollination drop of several gymnosperm species, Juniperus communis, Juniperus oxycedrus and Welwitschia mirabilis. Gonzalez-Teuber et al (2010) identified class I chitinase (GH19) in extrafloral nectar of Acacia species, and Escalante- Perez et al (2012) identified classes III (GH18), IV (GH19), and V (GH18) in extrafloral nectar of Populus trichocarpa.…”
Section: Introductionmentioning
confidence: 98%